Effects of Bitter Melon and a Chromium Propionate Complex on Symptoms of Insulin Resistance and Type 2 Diabetes in Rat Models - White, Pandora E.; Król, Ewelina; Szwengiel, Artur; Tubacka, Małgorzata; Szczepankiewicz, Dawid; Staniek, Halina; Vincent, John B.; Krejpcio, Zbigniew (Biological trace element research, 2021)
Trivalent chromium (Cr) and bitter melon ( Momordica charantia L., BM) have been shown to independently interact with the insulin signaling pathway leading to improvements in the symptoms of insulin resistance and diabetes in some animal models and human subjects. The aim of this study was to examine whether the combination of the two nutritional supplements could potentially have additive effects on treating these conditions in high-fat-fed streptozotocin (STZ)-induced diabetic rats. The experiment was conducted with 110 male Wistar rats divided into eleven groups and fed either a control or high-fat diet for 7 weeks. Half of the rats on the high-fat diet were injected with STZ (30 mg/kg body mass) to induce diabetes. The high-fat (HF) diets were then supplemented with a combination of Cr (as chromium(III) propionate complex, Cr3: either 10 or 50 mg Cr/kg diet) and bitter melon (lyophilized whole fruit: either 10 or 50 g/kg diet) for 6 weeks. After termination of the experiment, blood and internal organs were harvested for blood biochemical, hematological, and mineral (Cr) analyses using appropriate analytical methods. It was found that neither Cr(III) nor BM was able to significantly affect blood indices in HF and diabetic rats, but BM tended to improve body mass gain, blood glucose, and LDL cholesterol values, but decreased Cr content in the liver and kidneys of the Cr-co-supplemented type 2 diabetic model of rats. Supplementary Cr(III) had no appreciable effect on glucose and lipid metabolism in high-fat-fed STZ-induced diabetic rats. Supplementary BM fruit powder had some observable effects on body mass of high-fat-fed rats; these effects seem to be dampened when BM was co-administered with Cr. Cr(III) and BM appear to act as nutritional antagonists when both administered in food, probably due to binding of Cr by the polyphenol-type compounds present in the plant material. Graphical Abstract